High fodder value and feeding likelihood favour endozoochorous plant dispersal. (31st December 2016) - Gilhaus, Kristin; Freitag, Martin; Kunze, Svenja; Hölzel, Norbert
Abstract: Questions: In pasture‐dominated landscapes, endozoochory by large herbivores is an important vector of plant dispersal. Conditions influencing the potential for endozoochorous dispersal of plant species by grazers are, however, still poorly known. Here, we assess the impact of feeding habits and functional traits on the likelihood of endozoochorous dispersal by cattle (ruminants) and horses (non‐ruminants). Location: Pasture of 27 ha in NW Germany, year‐round grazed by free‐ranging cattle and horses. Methods: Vegetation relevés were established in 45 plots, from which dung samples of cattle and horses were collected. The number and composition of seedlings emerging from dung samples were compared with the vegetation of the study site in terms of plant functional trait composition. For the first time, feeding habits were included in the analysis. GLMs were used to identify traits that increased the potential for endozoochorous dispersal. Results: A total of 65 species germinated from the dung samples. These species had higher average fodder and nutrient indicator values than the species composition of the vegetation. In particular, species found in horse dung were more tolerant of grazing and had more elongated seeds. The likelihood of endozoochorous dispersal was higher for common than for rare species and was influenced by feeding habits. Conclusions: The likelihood of plant species being dispersed endozoochorously can be linked to different functional traits and is dependent on the type of grazer and the population size of target species in the vegetation. Differences between cattle and horses in seed dispersal may result from species‐specific grazing habits and different digestion modes. Abstract : Data on endozoochorous dispersal in a year‐round pasture were linked to feeding habits, vegetation composition and functional traits. The likelihood of being dispersed endozoochorously was dependent on the type of grazer and the population size of target species in the vegetation. Differences between cattle and horses in seed dispersal may result from species‐specific grazing habits and different digestion modes.